Propaganda and counter-terrorism : strategies for global change - Briant, Emma (Manchester University Press, 2015)
'This book offers a unique account of British and United States Governments' attempts to adapt their propaganda strategies to global terrorist threats in a post-9/11 media environment. It discusses Anglo-American coordination and domestic struggles that brought in far-reaching changes to propaganda. Changes that had implications for the structures of legitimacy yet occurred largely in isolation from public debate. The fast-paced evolution of the global information sphere prompted rapid development of practices that raise questions regarding their governance. Dr. Briant argues that independent and public reexamination of continuing strategy development is essential for government accountability and the formation of systems and policies that both respect citizens and build constructive foreign relations. This book's themes will engage a wide readership including scholars, PR professionals and government personnel' --Back cover.